Evaluating the effectiveness of using distance education from the point of view of the principals of public schools in the Directorate of Education – Irbid District - Al-Hinnawi, Naimeh Kbeah (Journal of Curriculum and Teaching Methodology, 2022)
This study aimed to evaluate the effectiveness of the use of distance education from the point of view of the principals of public schools in the Directorate of Education, Irbid District.The researcher used the descriptive survey method, and the tool consisted of a questionnaire of four fields, which were distributed to a stratified random sample of (115) male and female principals. The results showed that the school principals’ evaluation of the effectiveness of distance education teaching got an overall average (3.13 out of 5) with a (medium) degree of effectiveness, and at the level of the domains: the effectiveness of teaching came with the highest average (3.26), then the means and techniques with an average of (3.19) and the third field which is the interaction with an average of (3.01), and finally the evaluation with an average of (2.88), all of which evaluated the effectiveness of (medium). The results of the study also showed that there were statistically significant differences in the study sample’s estimates of the effectiveness of using distance education due to the effect of practical experience. The differences came in favor of (5) years or less in the means, techniques, interaction, and the total degree, and the differences came in favor of (6-10) years in Evaluation, the impact of the school level in favor of basic schools. There were no statistically significant differences due to the impact of the school’s location in all areas. And based on the results, the researcher made a number of recommendations to increase the effectiveness of the use of distance education in government schools in Irbid District and the whole Kingdom, in addition to suggestions for complementary studies in the subject.